Is the Brazilian made bioethics social? : A personal account - Zanella, Diego Carlos (Array, 2021)
This paper aims to present the panorama in which bioethics was found in Brazil. For this, exploratory descriptive and documentary research will be carried out on the emergence of bioethics as a field of research and its process of institutionalization in Brazil. In this sense, three facts are very significant: i) the creation of a bi-annual journal, Revista Bioética, published by the Federal Council of Medicine (CFM) in 1993; ii) the creation of the Brazilian Society of Bioethics (SBB) in 1995 to bring together researchers and people from different academic areas interested in bioethics; and iii) the edition of Resolution N.° 196 of October 10, 1996, of the National Health Council (CNS), which created the Brazilian Research Ethics System, that is, the Research Ethics Committees (CEP) and the National Research Ethics Commission (CONEP). These three facts will allow to identify which are the main defining elements and how they form the first theoretical models of Brazilian bioethics. Thus, this research will allow the building of a panorama of Brazilian bioethics, in which the characteristic notes of such a bioethical thought will be identified.